Regulators of Adult Hippocampal Neurogenesis - Dhaliwal, Jagroop (Université d'Ottawa / University of Ottawa, 2017)
One mechanism of plasticity within the adult mammalian brain is the dynamic process of adult neurogenesis that is functionally important in physiological and pathological conditions. During this process, neurons develop from adult neural stem cells (NSCs) via intermediate neural progenitors (NPCs) through several processes including proliferation, survival, differentiation, migration and integration. Despite neurogenesis during development sharing these same processes, there is growing evidence highlighting unique mechanisms that regulate adult versus embryonic neurogenesis. The studies in this thesis test the cell-intrinsic function of genes that have defined roles in embryonic neurogenesis and undefined roles in adult hippocampal neurogenesis using a combination of transgenic inducible mice and in vivo retroviral techniques. The first study examines the microtubule associated protein Doublecortin (DCX), which is transiently expressed by NPCs and is critical for neuronal migration. Our results show that, in the context of adult hippocampal neurogenesis, DCX is not required for the survival or differentiation of the NPCs within the subgranular zone (SGZ). The second study examines the functional role of the autophagy-associated gene 5 (Atg5) which is critical for embryonic neurogenesis and survival. Our findings demonstrate that the intracellular recycling process of autophagy is active throughout maturation of adult hippocampal NPCs and that ablation of Atg5 produces a drastic reduction in NPC survival, without altering the neuronal fate of these cells. The third study examines the requirement of the familial-Alzheimer’s disease associated genes, presenilin 1 and presenilin 2 (PS1 & PS2), which are critical for embryonic NSC maintenance and differentiation. Similar to the findings with DCX, our results demonstrate that presenilins are dispensable for adult neurogenesis. Altogether, these studies add to the growing evidence suggesting differences in the regulation of adult versus embryonic neurogenesis, and highlight autophagy as a novel regulator of survival for adult generated granule neurons in the hippocampus.
Keywords: Adult Neurogenesis; Presenilin; Autophagy; Atg5; Doublecortin; PS1 and PS2; Retrovirus; Transgenic inducible